Tight coupling between coral reef morphology and mapped resilience in the Red Sea. Issue 2 (30th April 2016) - Rowlands, Gwilym; Purkis, Sam; Bruckner, Andrew
Abstract: Lack of knowledge on the conservation value of different reef types can stymie decision making, and result in less optimal management solutions. Addressing the information gap of coral reef resilience, we produce a map-based Remote Sensed Resilience Index ( RSRI ) from data describing the spatial distribution of stressors, and properties of reef habitats on the Farasan Banks, Saudi Arabia. We contrast the distribution of this index among fourteen reef types, categorized on a scale of maturity that includes juvenile (poorly aggraded), mature (partially aggraded), and senile (fully aggraded) reefs. Sites with high reef resilience can be found in most detached reef types; however they are most common in mature reefs. We aim to stimulate debate on the coupling that exists between geomorphology and conservation biology, and consider how such information can be used to inform management decisions. Highlights: Production of a spatial index of coral reef resilience for the Farasan Banks The distribution of this index is compared between fourteen different reef types. Sites with high reef resilience can be found in most reef types. Sites with high reef resilience are most common in mature reefs. This information can be used to inform approaches to reef management.